DESIGN OF AN AUTOMATIC PENDULUM VELOCITY MEASURING DEVICE USING LIGHT SENSORS - Adiati, Rima Fitria; Haniyah, Astridea Salwa; Kartono, Agus; Syafutra, Heriyanto (Indonesian Physical Review, 2025)
The instantaneous velocity of an object is the rate of change of its position over an infinitesimally small-time interval, making direct measurement with tools like stopwatches impractical. Using two LDR sensors paired with an Arduino, it is possible to measure such small-time intervals effectively. Understanding the maximum velocity of a mathematical pendulum is critical for distinguishing between harmonic and non-harmonic oscillations. To validate the accuracy of the sensor-Arduino system, several experiments were conducted, including comparisons between Arduino measurements and those obtained from a movie tracker, as well as variations in sensor separation distances, initial oscillation angles, and pendulum rope lengths. Results showed a high level of agreement between Arduino and movie tracker measurements for pendulum crossing times. Additionally, the sensor-Arduino system successfully differentiated the effects of varying each parameter while holding others constant. The system demonstrated an accuracy of 97.86% for velocity measurements at a release angle of 5Â°, with an average recorded velocity of 23.350 m/s. These findings confirm the sensor-Arduino system's capability to reliably measure the velocity of a mathematical pendulum.